Safari pug : the dog who walked on the wild side - James, Laura, 1979- (James, Laura, 1979- Adventures of Pug., 2018)
Deciding that Pug needs to face his fears, Lady Miranda takes him to a safari park where he goes nose-to-nose with Florence, a rare white lion cub, but he soon realizes that lions may not be the most dangerous thing in the wildlife park.